2022
DOI: 10.3390/pharmaceutics14061150
|View full text |Cite
|
Sign up to set email alerts
|

Novel Eye Drop Delivery Systems: Advance on Formulation Design Strategies Targeting Anterior and Posterior Segments of the Eye

Abstract: Eye drops are the most common and convenient route of topical administration and the first choice of treatment for many ocular diseases. However, the ocular bioavailability of traditional eye drops (i.e., solutions, suspensions, and ointments) is very low because of ophthalmic physiology and barriers, which greatly limits their therapeutic effect. Over the past few decades, many novel eye drop delivery systems, such as prodrugs, cyclodextrins, in situ gels, and nanoparticles, have been developed to improve oph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 215 publications
1
6
0
Order By: Relevance
“…The PLGA-based system had similar performance to previous work, in terms of the delivery of pirfenidone from PLGA particles . The only significant difference between this system and the previous work was the addition of the poloxamers, with the thought that the poloxamers would facilitate uptake to the back of the eye if the nanoparticles were used in a drop formulation, as others have reported. , The poloxamers did not alter the release but did have an impact on loading. While the drop formulations of nanoparticles may have the potential for pirfenidone based on the substantial safety record of the drug since there is still a substantial percentage of particles that would enter the systemic circulation using these methods, there are inherent challenges in using degradable polyesters for delivery in the eye, particularly for diseases like AMD.…”
Section: Discussionsupporting
confidence: 63%
“…The PLGA-based system had similar performance to previous work, in terms of the delivery of pirfenidone from PLGA particles . The only significant difference between this system and the previous work was the addition of the poloxamers, with the thought that the poloxamers would facilitate uptake to the back of the eye if the nanoparticles were used in a drop formulation, as others have reported. , The poloxamers did not alter the release but did have an impact on loading. While the drop formulations of nanoparticles may have the potential for pirfenidone based on the substantial safety record of the drug since there is still a substantial percentage of particles that would enter the systemic circulation using these methods, there are inherent challenges in using degradable polyesters for delivery in the eye, particularly for diseases like AMD.…”
Section: Discussionsupporting
confidence: 63%
“…The absorption of drugs on the ocular surface is limited by various barriers, such as static (cornea, conjunctiva, sclera), dynamic (tear turnover, reflex blinking, conjunctival blood flow, and nasolacrimal drainage), metabolic barriers ( phase I & II enzymes, efflux pumps) and intraocular environment (blood-retinal and blood-aqueous barriers), resulting in extremely low drug bioavailability which is usually less than 5% and difficult to be delivered to the posterior segment of the eye. [32][33][34][35] After topical instillation, drugs may penetrate into the posterior segment via the corneal or/and conjunctival route. Drugs can penetrate through the cornea to the anterior chamber, then pass through the lens/iris to reach the vitreous and retina.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…69 Nanomicelles are emerging as a promising platform for the delivery of poorly water-soluble drugs to the eye due to their increased bioavailability, enhanced corneal permeation, and increased solubility and stability of drugs. [70][71][72][73] Zhao et al reported a nanomicelle drug delivery system made of a copolymer EPC (nEPC), comprising PEG, polypropylene glycol (PPG), and polycaprolactone (PCL) for the topical instillation of aflibercept to the posterior segment of the eye. nEPCs were made by concentrating EPC above the critical micelle concentration but below the concentration required for sol-gel transition.…”
Section: Nanomicellesmentioning
confidence: 99%
“…Tight junctions within this barrier also limit the entry of drugs from the blood into the retina. This work is adapted from [ 22 ], used under CC BY 4.0.…”
Section: Figurementioning
confidence: 99%